Gendered political space: civil society, contingency theory, and the substantive representation of women. Issue 2 (2nd April 2016) - Chaney, Paul
ABSTRACT: Whilst existing civil society studies generally fail to systematically examine the way that contextual factors shape women's representation in the civil sphere, political science has predominantly focused on legislative settings. This article responds to the resultant knowledge-gap by examining the hitherto underexplored role of civil society as a political space integral to the substantive representation of women (SRW)—or, the process by which women's concerns are advanced in policy and politics. The article uses grounded theory in order propose a systematic analytical model showing how the SRW is a contingent process whereby the motives of civil society organizations are translated into action repertoires shaped by three (non-discrete) spheres: political, socioeconomic, and organizational. Its wider contribution to civil society scholarship is in highlighting how civil society is a complex, heterogeneous political space wherein SRW claims-making requires cognizance of the co-presence of contingent factors that offer immanent explanatory power.